Corrosion behavior of friction stir welded AZ31B Mg alloy - Al6063 alloy joint. Issue 1 (31st December 2016) - Ratna Sunil, B.; Pradeep Kumar Reddy, G.
Abstract: In the present work, AZ31B Mg alloy and Al6063 alloy-rolled sheets were successfully joined by friction stir welding. Microstructural studies revealed a sound joint with good mechanical mixing of both the alloys at the nugget zone. Corrosion performance of the joint was assessed by immersing in 3.5% NaCl solution for different intervals of time and the corrosion rate was calculated. The joint has undergone severe corrosion attack compared with both the base materials (AZ31B and Al6063 alloys). The predominant corrosion mechanism behind the high corrosion rate of the joint was found to be high galvanic corrosion. From the results, it can be suggested that the severe corrosion of dissimilar Mg–Al joints must be considered as a valid input while designing structures intended to work in corroding environment.